Determination of ochratoxin A content in wheat bread samples collected from the Algarve and Bragança regions, Portugal: Winter 2007 - Bento, J. M. V. (2009)
http://www.sciencedirect.com/science/article/B6W6H-4TX33XB-1/2/609b7e7d0247810aab7cad1fae1f851b